Sport czyni ludzi lepszymi - o wartościach w czasopiśmie "Olimpionik" = Sport makes people better - about values in magazine "Olimpionik" - Grochala, Beata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents values promoted in the "Olimpionik" magazine for children and youth published by Polish Olympic Comitee (PKOl). The magazine presents the beauty of sport, fight, competition combined with patriotism, overcoming your own barriers and fair play competition.
Keywords: sport; ruch olimpijski; wartości; czasopismo młodzieżowe; czasopismo dziecięce; Olimpic movement; values; magazines for children and youth